Direct Social Action, Welfare Retrenchment and Political Identities. Coping with the Crisis and Pursuing Change in Italy - Zamponi, Lorenzo (PArtecipazione e COnflitto, 2019)
In the context of the economic crisis, research on collective action has increasingly focused direct social actions, that escape the traditional state-addressing repertoires of action and focus on a self-changing society: boycotts, solidarity action, political consumerism, alternative finance (e.g. crowdfunding, food banks), collective purchasing groups, occupations, self-management, free legal advice and medical services, to mention just a few. This article aims to address the issue of direct social action as a response to welfare retrenchment in the context of the economic crisis in Italy, focusing in particular on actors with a background in protest and social movement milieus. How do these actors keep protest and direct social action together? How do they justify the choice to engage in direct social action? How do they make sense of the contradiction between service-providing and claim-making? And what are the consequences of the choice of these forms of action on their identity? The article answers these questions through the analysis of 20 qualitative interviews to representatives of organisations engaging in direct social actions in Italy. The analysis shows that investigating the transition in the form of action as a political process, rooted in the decline of political participation, and aiming at reconstructing identity and politicisation, is helpful to understand how actors address the risk of substitution and to assess the outcomes of direct social action